Pengaruh Lama Penggunaan Minyak Goreng Kelapa Sawit terhadap Karakterisasi Trigliserida dan Crude Glycerol: The Effect of Long Use of Palm Cooking Oil on the Characterization of Triglycerides and Crude Glycerol - Febiola, Intan; Hanum, Galuh Ratmana (Universitas Muhammadiyah Sidoarjo, 2018)
The price of cooking oil has been increasing every year. Repetaed of using cooking oil will appearance negative impact for healthy and positive impact for biodiesel industry as raw material glycerol. This research aim to knowing the effect of times palm cooking oil for characteristic triglyceride and crude glycerol of pH, flavour, colour, density, and content for daily use. The category of sample is 0 day as control, 4 days as P1, 8 days as P2, 12 days as P3 with experiment laboratory method. The statistic was perfomed by binomial test for flavour, kruskal-wallis test for colour, and one way anova for pH, density, and content. If any treatment effect was continued with post hoc test. The result showed as control; P1; P2; P3 of characteristic triglyceride respectively for pH are 6.67; 6.13; 6.13; 5.88; for flavour is not flavourfull for all type; for colour are yellow; yellow; clear-yellow; brownish-yellow; for density are 0.740; 0.789; 0.747; 0.734; and content are 93.8; 83.9; 80.2; 75.3. whereas characteristic of crude glycerol respectively for pH are 5.92; 6.18; 6.35; 6.28; for flavour is not flavourfull for all type; for colour are yellow; yellow; red-yellow; red; for density are 1.058; 0.961; 1.021; 1.036; and content are 34.4; 46.3; 51.1; 58.4. The result of statistic is times palm cooking oil not influence for pH, but influence significantly for flavour, colour, density, and content.